2015
DOI: 10.1186/s13578-015-0003-4
|View full text |Cite
|
Sign up to set email alerts
|

Mediation of exogenous hydrogen sulfide in recovery of ischemic post-conditioning-induced cardioprotection via down-regulating oxidative stress and up-regulating PI3K/Akt/GSK-3β pathway in isolated aging rat hearts

Abstract: The physiological and pathological roles of hydrogen sulfide (H2S) in the regulation of cardiovascular functions have been recognized. Cystathionine gamma-lyase (CSE) is a major H2S-producing enzyme in cardiovascular system. Ischemic post-conditioning (PC) provides cadioprotection in young hearts but lost in the aging hearts. The involvement of H2S in the recovery of PC-induced cardioprotection in the aging hearts is unclear. In the present study, we demonstrated that ischemia/reperfusion (I/R) decreased H2S p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 50 publications
(66 reference statements)
2
63
1
Order By: Relevance
“…This could explain the increase in cytotoxicity with increasing level of doping observed in our study. This effect was also observed in another study54 evaluating the cytotoxicity of chemically synthesized zinc-doped iron oxide nanoparticles. A dose dependant decrease in mitochondrial metabolic activity (as measured via MTT) and increase in membrane damage (as measured via the LDH assay) was observed in human lung epithelial (A549), skin epithelial (A431) and liver (HepG2) cells.…”
Section: Discussionsupporting
confidence: 70%
“…This could explain the increase in cytotoxicity with increasing level of doping observed in our study. This effect was also observed in another study54 evaluating the cytotoxicity of chemically synthesized zinc-doped iron oxide nanoparticles. A dose dependant decrease in mitochondrial metabolic activity (as measured via MTT) and increase in membrane damage (as measured via the LDH assay) was observed in human lung epithelial (A549), skin epithelial (A431) and liver (HepG2) cells.…”
Section: Discussionsupporting
confidence: 70%
“…This was supported by the observation that GYY4137 increased Akt phosphorylation in left ventricular myocardium during early reperfusion, an effect abolished by LY294002. Li et al (2015a) showed that NaSH at reperfusion limited cell death by activating PI3K/Akt pathway in aging rat heart and cardiomyocytes. However, Lambert et al (2014) demonstrated that in diabetic rats NaSH-induced postconditioning might signal through the other arm of the RISK pathway, namely ERK1/2.…”
Section: Gyy4137 Postconditioning Activates Pi3k/akt Signallingmentioning
confidence: 99%
“…Both H 2 S and garlic oil have been shown to be cardioprotective (6,13,18,25,26,31,35,67) and contribute to ischemic conditioning (45,65). Both are anti-inflammatory (7,56), anti-atherosclerotic (29,33,62), induce Ca 2ϩ influx in astrocytes (22), and have been reported to act as potent antioxidants (5,9,15,21,49,53,59,60) and to decrease oxidative stress (28,31,68).…”
mentioning
confidence: 99%